Pemilahan Sampah dengan Cara Paksa Pilah Sampah dari Rumah - Rahmawati Eka Dewi; Nur Setiyaningrum; Ayuning Sekar Hapsari; Fajar Gemilang Pradana (Universitas Muhammadiyah Yogyakarta, 2022)
The waste problem is an urgent issue that has not been resolved in various regions until now. To overcome this problem, the Head of Subdistrict Banjarsari took the initiative to create a PAPISARIMAH (Forced Sorting Garbage From Home) program. However, not all residents are well-informed about the program. This observation aimed to educate residents to sort organic and inorganic waste from their homes to make it easier to classify waste when transported to the TPA. This service was carried out in Tapen Village RW 6, Nusukan, Banjarsari District, Surakarta. The implementation was conducted through socialization which consists of (1) lecture method, (2) demonstration method, (3) question and answer, and (4) direction. The result of this service, namely the socialization of sorting waste in Tapen Village, received a positive response from the residents, and more residents became self-aware of sorting waste from their homes. Also, the residents intend to sustain the program by gradually forming a Waste Bank. Meanwhile, officers went around every house to pick up inorganic waste, such as plastic bottles, to sell to collectors.